2015
DOI: 10.1038/srep12032
|View full text |Cite
|
Sign up to set email alerts
|

T2D and Depression Risk Gene Proteasome Modulator 9 is Linked to Insomnia

Abstract: Insomnia increases type-2 diabetes (T2D) risk. The 12q24 locus is linked to T2D, depression, bipolar disorder and anxiety. At the 12q24 locus, the Proteasome-Modulator 9 (PSMD9) single nucleotide polymorphisms (SNPs) rs74421874 [intervening sequence (IVS) 3+nt460-G>A], rs3825172 (IVS3+nt437-C>T) and rs14259 (E197G-A>G) are linked to: T2D, depression, anxiety, maturity-onset-diabetes-of the young 3/MODY3, obesity, waist circumference, hypertension, hypercholesterolemia, T2D-macrovascular disease, T2D-microvascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…We highlighted the possible gene pathways and mechanisms related to the neuro‐endocrine cortisol pathway impairment contributing to the clinical association of MDD and T2D (Gragnoli, , ). As previously mentioned, we also reported PSMD9 in linkage with T2D (Gragnoli, ), depression (Gragnoli, ), and the depression‐associated mental traits of generalized anxiety disorder (Gragnoli, ), and insomnia (Hao et al, ). PSMD9 is a highly concentrated ubiquitous PDZ‐domain‐containing chaperone of the 26S proteasome complex assembly and is an insulin gene transcription coactivator highly transcribed in pancreatic islets (Thomas, Yao, Tenser, Wong, & Habener, ).…”
Section: Mental and Metabolic Comorbiditysupporting
confidence: 68%
See 1 more Smart Citation
“…We highlighted the possible gene pathways and mechanisms related to the neuro‐endocrine cortisol pathway impairment contributing to the clinical association of MDD and T2D (Gragnoli, , ). As previously mentioned, we also reported PSMD9 in linkage with T2D (Gragnoli, ), depression (Gragnoli, ), and the depression‐associated mental traits of generalized anxiety disorder (Gragnoli, ), and insomnia (Hao et al, ). PSMD9 is a highly concentrated ubiquitous PDZ‐domain‐containing chaperone of the 26S proteasome complex assembly and is an insulin gene transcription coactivator highly transcribed in pancreatic islets (Thomas, Yao, Tenser, Wong, & Habener, ).…”
Section: Mental and Metabolic Comorbiditysupporting
confidence: 68%
“…Thus, at least one or a few genes and/or gene variants across this locus are expected to explain the pleiotropic or comorbid possibly unitarian linkage of the above‐mentioned phenotypes. One of these genes may be the PSMD9 gene as previously reported by us to be in linkage with several of the 12q24 linked phenotypes (T2D, depression, anxiety, hypertension, microvascular disease, retinopathy, hypercholesterolemia, overweight condition, and macrovascular disease) (Gragnoli, , , , , , , , , ; Gragnoli & Cronsell, ; Hao, Haas, Wu, & Gragnoli, ), and insomnia. Of note, PSMD9 has been reported by other groups as one of the top risk genes for MDD (Wong et al, , ) and SCZ (Lee et al, ).…”
Section: Mental and Metabolic Comorbiditymentioning
confidence: 91%
“…PSMD9 is a transcriptional regulator of insulin gene transcription and variants can contribute to type 2 DM by causing beta-cell dysfunction; therefore, single nucleotide polymorphisms (SNP) of transcriptional regulators can alter the expression of neurotransmitters, and neuronal ion channels and their receptors, which can lead to DSPN and neuropathic pain ( 3 , 11 , 12 ). Earlier studies reported that PSMD9 rs14259 (E197G-A >G) polymorphism is associated with type 2 DM, depression, schizophrenia, anxiety, maturity-onset diabetes-of the young 3/MODY3, obesity, increased waist circumference, hypertension, hypercholesterolemia, type 2 DM-macrovascular diseases, type 2 DM-microvascular disease, type 2 DM-neuropathy, type 2 DM-carpal-tunnel syndrome, type 2 DM-nephropathy, type 2 DM-retinopathy, and non-diabetic retinopathy ( 13 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Proteasome modulator 9 (PSMD9) is a part of the 26S proteasome complex degrading intracellular proteins in the immune response and antigen presentation by MHC class I cells. It was demonstrated that PSMD9 inhibited tumor necrosis factor α (TNF-α)-mediated NF-kB activation via inhibition of nuclear factor kBα (IkBα) proteasome degradation (Hao et al, 2015). TNF-α is one determinant of AD and T2DM onset and progression (Tsutsui and Hays, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…TNF-α is one determinant of AD and T2DM onset and progression (Tsutsui and Hays, 2018). In addition, the proteasome-mediated proteolysis plays a recognized role in neuronal development, synaptic plasticity, and protein quality control (Hao et al, 2015). Thus, PSMD9 variants might play a role in neuroinfl ammation and many neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%